A trifecta of g-C3N4: enhanced visible-spectrum absorption, increased structural distortion and boosted electronic-transfer dynamics. Issue 7 (4th January 2021) - Liu, Huanhuan; Wang, Haifei; Zhang, Fu; Xue, Jierui; Zhang, Jihua; Zhang, Genqiang
Abstract : CNNC with enhanced visible-spectrum absorption, increased structural distortion and boosted electronic-transfer dynamics results in prominent photocatalytic performance. Abstract : Porous spheres of graphitic carbon nitride (CN) with N-doped carbon species (CNNC) were synthesized under mild conditions by calcining a melamine–cyanic acid precursor containing a certain amount of PVP. Introduction of N-doped carbon led to enhancement of visible-spectrum utilization and greater distortion of the plane of g-C3 N4 . These actions greatly improved the separation efficiency of photogenerated electrons–holes pairs. The photocatalytic hydrogen evolution (PHE) performance was 7.5-fold higher than that of CN and 2.2-fold that of the sample without plane distortion (CNNC- U ). As bifunctional photocatalysts, the photoelectrons were applied to reduce water to hydrogen, whereas the holes were used for benzaldehyde production by oxidation of benzyl alcohol. The rates of PHE and benzaldehyde production for CNNC-0.1 could reach ∼3.12-fold and ∼3.17-fold higher than that for CN, respectively. This work provides a new strategy to enhance visible-spectrum absorption and manipulation of layer structures to boost electronic-transfer dynamics.